2013
DOI: 10.1186/1478-811x-11-51
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of aggressive amoeboid sarcoma cells is dependent on Rho/ROCK/MLC signaling

Abstract: BackgroundAlthough there is extensive evidence for the amoeboid invasiveness of cancer cells in vitro, much less is known about the role of amoeboid invasiveness in metastasis and the importance of Rho/ROCK/MLC signaling in this process.ResultsWe analyzed the dependence of amoeboid invasiveness of rat and chicken sarcoma cells and the metastatic activity of chicken cells on individual elements of the Rho/ROCK/MLC pathway. In both animal models, inhibition of Rho, ROCK or MLC resulted in greatly decreased cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The transition to amoeboid motility (mesenchymal‐to‐amoeboid transition; MAT), can be induced experimentally by inhibiting metalloproteinase activity [Wolf et al., 2003a,b; Kosla et al., ; Taddei et al., ], disrupting cell–substrate adhesions [Wolf et al., ; Carragher et al., ; Van Goethem et al., ; Ehrbar et al., ; Liu et al., ], inhibiting Arp2/3 complex‐dependent actin polymerisation in lamellipodia [Derivery et al., ; Bergert et al., ; Beckham et al., ], or shifting a balance between actin polymerisation‐driven protrusion and actomyosin‐dependent contractility by altering Rho‐family small GTPases activity [Sahai and Marshall, ; Sanz‐Moreno, V., ; Parri et al., ; Bergert et al., ]. Thus, it appears that under conditions unfavourable for lamellipodium formation, some tumour cells switch to amoeboid motility to bypass the inhibition which leads to greater autonomy of cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…The transition to amoeboid motility (mesenchymal‐to‐amoeboid transition; MAT), can be induced experimentally by inhibiting metalloproteinase activity [Wolf et al., 2003a,b; Kosla et al., ; Taddei et al., ], disrupting cell–substrate adhesions [Wolf et al., ; Carragher et al., ; Van Goethem et al., ; Ehrbar et al., ; Liu et al., ], inhibiting Arp2/3 complex‐dependent actin polymerisation in lamellipodia [Derivery et al., ; Bergert et al., ; Beckham et al., ], or shifting a balance between actin polymerisation‐driven protrusion and actomyosin‐dependent contractility by altering Rho‐family small GTPases activity [Sahai and Marshall, ; Sanz‐Moreno, V., ; Parri et al., ; Bergert et al., ]. Thus, it appears that under conditions unfavourable for lamellipodium formation, some tumour cells switch to amoeboid motility to bypass the inhibition which leads to greater autonomy of cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…ROCK and MRCK have been shown to phosphorylate MLC and have been implicated in regulation of cell contractility [15][16][17]. The amoeboid mode of invasion is primarily dependent on ROCK activity to generate strong contractile forces and is independent of protease activity [18][19][20], whereas the mesenchymal mode of cell invasion depends on the activity of MRCK to generate contractile forces [21]. Importantly, studies demonstrate that cancer cells often switch between these two mechanisms when an individual mode of migration/invasion is blocked (reviewed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that the model can be used to identify sarcoma patients at high risk and enabling early interventions to improve the prognosis. Among 19 IRGs enrolled in risk signature, VEGFA, CYR61, and RHOA have con rmed to be related to the pathogenesis or prognosis of sarcoma [38][39][40][41]. It was reported that VEGFA is a potential neovascular regulatory factor that promotes tumor growth and metastasis through its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of CYR61 is associated with the aggressiveness of osteosarcoma in different pre-clinical models and patient tumor samples, and CYR61 triggers osteosarcoma metastasis and spread through an IGF1Rβ-dependent EMTlike process [44]. The metastasis of invasive amoebic sarcoma cells depends on the Rho / Rock / MLC signal, and RHOA overexpression is related to tumor cell invasion and migration [41]. The relationship between the remaining 16 genes and sarcoma has few been reported, however, most of them have been con rmed to be associated with other tumors, which suggested that these genes also play essential roles in sarcoma.…”
Section: Discussionmentioning
confidence: 99%